Innovation and Paradigm Shift in Devecser School District From Point of View of the Pedagouge (Training and Practice : Journal of Educational Sciences, 2016)
More and more often we notice the seemingly trivial word „innovation” which has been integrated into pedagogy for decades. One of the key focus of my interest is the Social Renewal Program and how this kind of development is realized in school. I have conducted a research in several places. In this case not only one institution, but a whole school district answered my question. I carried out survey in the local schools. Who, on what level, how and in what are able te be innovative? I also studied the role of the headmaster or the director of the school district in the process, which will be presented in later studies. My results represent well that the educators intend to change their perspective, renew their methodology, bring to the fore the life long learning approach, and especially that the motor of institutional renewal is always a good leader.